2022
DOI: 10.3389/fped.2022.1062766
|View full text |Cite
|
Sign up to set email alerts
|

S945L-CFTR molecular dynamics, functional characterization and tezacaftor/ivacaftor efficacy in vivo and in vitro in matched pediatric patient-derived cell models

Abstract: Cystic Fibrosis (CF) results from over 400 different disease-causing mutations in the CF Transmembrane Conductance Regulator (CFTR) gene. These CFTR mutations lead to numerous defects in CFTR protein function. A novel class of targeted therapies (CFTR modulators) have been developed that can restore defects in CFTR folding and gating. This study aimed to characterize the functional and structural defects of S945L-CFTR and interrogate the efficacy of modulators with two modes of action: gating potentiator [ivac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 72 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…The simulation methodologies for this study are the same as those used previously ( Allan et al, 2022 ; Wong et al, 2022a ; Wong et al, 2022b ). In brief, an extended model of the CFTR protein bound to ATP under phosphorylating conditions (PDB ID: 6MSM) was embedded in a 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) model bilayer then solvated with a solution containing 150 mmol KCl.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulation methodologies for this study are the same as those used previously ( Allan et al, 2022 ; Wong et al, 2022a ; Wong et al, 2022b ). In brief, an extended model of the CFTR protein bound to ATP under phosphorylating conditions (PDB ID: 6MSM) was embedded in a 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) model bilayer then solvated with a solution containing 150 mmol KCl.…”
Section: Methodsmentioning
confidence: 99%
“…Various patient derived cell models [reviewed in (10)] have been shown to replicate the genetic makeup of the individual they were created from. Importantly, CFTR functional testing in patient-derived cell models correlates with the in vivo clinical outcomes for that patient ( Dekkers et al, 2016 ; McGarry et al, 2017 ; Mutyam et al, 2017 ; McCarthy et al, 2018 ; Phuan et al, 2021 ; Terlizzi et al, 2021 ; Allan et al, 2022 ; Ciciriello et al, 2022 ). As such, they are useful tools to predict patient responsiveness to CFTR modulators and characterize rare mutations ( Awatade et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The reanalysis of cilia is often necessary following HNE cell culture and differentiation at the air–liquid interface to investigate the potential impact of secondary infections on CBF, which can modify ciliary function and lead to the potential misinterpretation of results in PCD assessment. Beyond PCD, HNE cell cultures have become increasingly important for diagnosis and studying the pathophysiology of, and developing drugs for, other airway diseases, such as allergic rhinitis, asthma and cystic fibrosis (CF) [ 9 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro assessment of CFTR modulator efficacy in patient-derived cell models has accelerated drug regulatory processes and provided access to personalized treatment to individuals who would otherwise be ineligible for approved modulator therapy [ 20 , 21 , 22 ]. Several studies comparing in vitro and in vivo CFTR function reported a correlation between the two; however, the sample size of the studies was relatively small [ 20 , 23 , 24 , 25 ]. A recent study reported that patient-derived cell models could identify modulator-responsive patients but may not accurately predict the magnitude of clinical benefit [ 26 ].…”
Section: Introductionmentioning
confidence: 99%